2002
DOI: 10.1128/aem.68.7.3238-3242.2002
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Microbial Flora in a Cattle Feedlot

Abstract: A total of 1,408 cattle held in eight commercial feedlot pens were used to examine the quantity and diversity of microorganisms in cattle feedlot air. The effect of two feeding patterns on the generation of airborne dust and the total numbers of microorganisms was also examined (four feedlot pens/treatment). Microbial samples were collected, and dust particles that were 2.5 m or less in diameter were measured with a Dustrak monitor during the evening dust peak for 4 days at sites both upwind and downwind of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 20 publications
3
53
0
2
Order By: Relevance
“…observed in both swine facilities were similar to those of swine gastrointestinal tracts (Leser et al 2002;SnellCastro et al 2005) and swine confinement buildings (Cormier et al 1990;Crook et al 1991;Predicala et al 2002;Nehme et al 2008). The phylogenetic types of organisms observed in the dairy samples were similar to those reported in the feces of dairy cows (Dowd et al 2008) and cultured in a previous aerosol study of cattle feedlots (Wilson et al 2002). Particular species of organisms and their proportions, however, differ among the various dairy studies.…”
Section: Discussionsupporting
confidence: 76%
“…observed in both swine facilities were similar to those of swine gastrointestinal tracts (Leser et al 2002;SnellCastro et al 2005) and swine confinement buildings (Cormier et al 1990;Crook et al 1991;Predicala et al 2002;Nehme et al 2008). The phylogenetic types of organisms observed in the dairy samples were similar to those reported in the feces of dairy cows (Dowd et al 2008) and cultured in a previous aerosol study of cattle feedlots (Wilson et al 2002). Particular species of organisms and their proportions, however, differ among the various dairy studies.…”
Section: Discussionsupporting
confidence: 76%
“…These trends are not just specific to Idaho; however, as other states and countries are experiencing increases in the number of CAFOs. As a result of high stocking densities at CAFOs, there is a concern over the release of bioaerosols, since they may cause adverse health effects in animals and workers (Lacey and Dutkiewicz 1994;Wilson et al 2002;Rule et al 2005;Heederik et al 2007;Spaan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of suspension in the air after being shed in feces and causing disease has already been described for other bacteria in farm animals (Wathes et al 1989;Hardman et al 1991;Wilson et al 2002). In animal housings, it has been shown that bacteria become airborne together with skin cells, hair, feed, bedding, and excretion particles in the form of dust and move through the barn (Collins and Algers 1986).…”
Section: Aerosol Transmission Of Infectious Diseasementioning
confidence: 92%